VD_FINDINFO Arrêt / 2018 / 971 vom 28. November 2018 - VD Tribunal cantonal (2018)
AM, LISTE DES SPÉCIALITÉS, INCONTINENCE, REJET DE LA DEMANDE, MAXIMUM | 25 al. 2 let. b LAMal, 33 al. 1 LAMal, 33 al. 5 LAMal, 52 al. 1 let. a LAMal, 52 al. 1 let. b LAMal, 34 OAMal, 20 OPAS, 24 OPAS, 82 LPA-VD